2007
DOI: 10.1016/j.jmb.2007.03.078
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Inhibition of Antibody-based Inhibitors of Membrane-type Serine Protease 1 (MT-SP1)

Abstract: SummaryThe mechanisms of inhibition of two novel scFv antibody inhibitors of the serine protease MT-SP1/ matriptase reveal the basis of their potency and specificity. Kinetic experiments characterize the inhibitors as extremely potent inhibitors with K I 's in the low picomolar range that compete with substrate binding in the S1 site. Alanine scanning of the loops surrounding the protease active site provide a rationale for inhibitor specificity. Each antibody binds to a number of residues flanking the active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
60
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 45 publications
0
60
1
Order By: Relevance
“…In the latter, the protruding domains encoded by the ultralong, up to 60-residue, CDR-H3s are frequent (45,46). In agreement, structural studies of the inhibitory antibodies isolated from human naive libraries also suggested that insertion of the long CDR-H3 variable loops (up to 19 residues) into the substrate-binding pocket is required to achieve efficient inhibition of membrane type serine protease 1 (matriptase) (37,47). Although the alternative inhibitory mechanisms are also well known, including those mechanisms that inactivate enzymes by inducing conformational changes or by blocking substrate access (48,49), multiple inhibitory antibodies exhibit unusually long CDR-H3s, implying that the extended CDR-H3s are vital for enzyme inhibition.…”
Section: Discussionmentioning
confidence: 69%
“…In the latter, the protruding domains encoded by the ultralong, up to 60-residue, CDR-H3s are frequent (45,46). In agreement, structural studies of the inhibitory antibodies isolated from human naive libraries also suggested that insertion of the long CDR-H3 variable loops (up to 19 residues) into the substrate-binding pocket is required to achieve efficient inhibition of membrane type serine protease 1 (matriptase) (37,47). Although the alternative inhibitory mechanisms are also well known, including those mechanisms that inactivate enzymes by inducing conformational changes or by blocking substrate access (48,49), multiple inhibitory antibodies exhibit unusually long CDR-H3s, implying that the extended CDR-H3s are vital for enzyme inhibition.…”
Section: Discussionmentioning
confidence: 69%
“…The cytochrome c can activate caspase-9 with subsequent caspase-3 that results in DNA fragmentation in mammalian cells [38]. It has been reported that the antibody of specific protein suppresses the function of corresponding antigen by blocking access to the catalytic site [85,86]. In this study, Anti-Cyt C inhibited the • OH-induced activation of caspase-9 in the erythrocytes.…”
Section: • Oh-induced Apoptosis In Fish Erythrocytesmentioning
confidence: 59%
“…Although a relatively small molecule (∼18-25kD), a scFv retains the specificity of the parent antibodies from which it was derived. Currently, specific scFvs are in use in vitro that inhibit proteases such as membrane type serine protease-1, which has been implicated in ovarian and prostate tumor progression (Farady et al, 2007), as well as to study the pleiotropic functions of substances such as IL-13, to better understand their role in immune function (Knackmuss et al, 2007).…”
Section: Introductionmentioning
confidence: 99%